Identifying the Acute Effects of Plyometric and Contrast Training on Acceleration and Agility in Young Rugby Players: A Randomized Controlled Trial - Saha, Sohom; Obhrai, Simran; Astuti, Yuni; Manamkandath, Mohamed Prince; Dhoni, Kamal (Physical Education Theory and Methodology, 2025)
Objectives. The present study examined the impact of a single session of plyometric training (PT) and contrast training (CT) on speed, agility, and power in young rugby players. The objective of this study was to ascertain which method produced better immediate improvements. Materials and methods. Thirty male rugby players at the national level (average age 14.3 years, height 1.51 meters, weight 48.63 kg) took part in the study. The participants were randomly divided into two groups: 15 individuals were assigned to a plyometric training plan, while the remaining 15 followed a contrast training routine. Before and after the training session, each athlete was subjected to testing for sprint speed (5m, 10m, and 20m), agility (assessed using the Illinois Agility Test), jump height (measured via the countermovement jump, CMJ), and explosive leg power (evaluatedwith reactive strength index, RSI). The plyometric protocol consisted of depth jumps, bounding, hurdle hops, lateral bounds, and spring-loaded drop jumps, while the contrast protocol paired heavy resistance exercises (85% 1RM) with biomechanically similar plyometric movements. Results. Both interventions produced significant acute improvements across all performance metrics (p<0.05). The CTG demonstrated superior enhancements compared to the PTG in 5m sprint time (-6.14% vs. -3.53%, p<0.001, η²p=0.79), 10m sprint time (-5.37% vs. -3.76%, p<0.048, η²p=0.68), 20m sprint time (-3.90% vs. -2.60%, p<0.019, η²p=0.18), agility time (-4.95% vs. -3.09%, p<0.001, η²p=0.94), RSI (+8.60% vs. +5.91%, p<0.001, η²p=0.82), and CMJ height (+7.40% vs. +5.79%, p<0.001, η²p=0.36). Conclusions. The study concludes that both training modalities acutely enhanced acceleration, agility, and power performance in young rugby players. However, contrast training produced significantly greater improvements across all metrics. The findings indicate that contrast training could be more useful than plyometric training for boosting explosive strength in young rugby players following a single session. This may be associated with triggering stronger short-term improvements in muscle performance.